2020
DOI: 10.1590/1984-0462/2020/38/2018178
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Pain: Characterization of the Physiotherapist’s Perception in the Neonatal Intensive Care Unit

Abstract: Objective: To describe the perception of physiotherapists in neonatal units regarding pain, the use of measurement scales and strategies that minimize pain. Methods: Interviews were conducted with physiotherapists in hospitals with neonatal units between 2013 and 2015 in Rio de Janeiro. The questions concerned the knowledge of the feeling of pain, from its recognition to its care or treatment. The description of the results was done by comparing public and private hospitals (Fisher’’s Exact exact Testtest),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
2
0
3
Order By: Relevance
“…Among the painful procedures, venepuncture and blood collection were considered the most common procedures that cause pain. 44 Neonates received few pain relief measures during hospitalization in NICUs. 45 An investigation in Brazil showed that in those preterm infants investigated, daily average painful interventions were 5.37, while the neonates with invasive ventilation were most exposed to painful procedures (71.2%), but only 44.9% received pain relief interventions.…”
Section: The Practices Of Neonatal Analgesia In Different Countriesmentioning
confidence: 99%
“…Among the painful procedures, venepuncture and blood collection were considered the most common procedures that cause pain. 44 Neonates received few pain relief measures during hospitalization in NICUs. 45 An investigation in Brazil showed that in those preterm infants investigated, daily average painful interventions were 5.37, while the neonates with invasive ventilation were most exposed to painful procedures (71.2%), but only 44.9% received pain relief interventions.…”
Section: The Practices Of Neonatal Analgesia In Different Countriesmentioning
confidence: 99%
“…Os neonatos prematuros são neurologicamente imaturos, mais suscetíveis aos efeitos danosos dos procedimentos dolorosos, o que justifica a importância do manejo da dor no período neonatal (Barandouzi et al, 2020). Já se sabe que essa falha no manejo da dor favorecerá alterações no desenvolvimento durante a primeira infância, exercendo efeitos prejudiciais permanentes nestas crianças, especialmente nos prematuros extremos, desde alterações no neurodesenvolvimento ou mesmo as síndromes metabólicas (Miatello et al, 2019;Gimenez et al, 2020).…”
Section: Introductionunclassified
“…Partindo dessa visão holística, a dor pode ser identificada e cuidada de forma que minimize os traumas que o paciente, neonato ou idoso, possa sentir, favorecendo o seu tratamento de forma mais humana. Por ser a dor única e subjetiva, torna-se mais difícil de ser avaliada no RN, pois existe uma ausência de capacidade de verbalização e experiências prévias de dor, que levariam a comparação e descrição dessa sensação (Gimenez et al, 2020) Atualmente, a dor é considerada como quinto sinal vital, assim para sua mensuração nos neonatos as expressões faciais são consideradas, juntamente com o uso de instrumentos que possam verificar o desconforto, propondo, assim, intervenções eficazes. Perceber e intervir a sensação dolorosa, proporcionará conforto e ajudará a promoção do bem-estar do prematuro (Gimenez et al, 2020;Bottega et al, 2010).…”
Section: Introductionunclassified
“…Thus, these matters are extremely important for the multidisciplinary team, especially nurses, as they generate sensitivity when observing changes that are considered, by many professionals, as a challenge during the assessment, treatment and pain relief in newborns, in order to enable humanized care (8,(11)(12)(13)(14) .…”
Section: Introductionmentioning
confidence: 99%